Strategies for coordinating experimentation and modeling in integrative systems biology. Issue 4 (27th March 2014) - MacLeod, Miles; Nersessian, Nancy J.
ABSTRACT In this paper, we provide a novel analysis of the affordances and trade‐offs of different strategies for integrating model‐building and experimentation in integrative systems biology. Unimodal strategies rely on collaboration between experimenters and modelers in distinct laboratories. In a bimodal strategy modelers perform their own experiments. Each option has advantages and challenges. In the case of the labs we studied, the choice of strategy often depends on preferences held by lab directors as to the strategy that best achieves certain philosophical objectives concerning what they see as the aims of modeling in systems biology and the epistemic standards to apply to it. We identify an important connection between philosophical divisions in systems biology and the structure of research in systems biology. Better knowledge of these strategies and their philosophical motivations provide insight behind the diversifying structure of the field, and can help lab directors understand the challenges their researchers face, as well as the training and lab organization options available. J. Exp. Zool. (Mol. Dev. Evol.) 322B: 230–239, 2014. © 2014 Wiley Periodicals, Inc.